Hybrid parenthood: circulation, appropriation, and commercialization of bio raw materials - Izrael, Estefania; Ayala, Estefania; Roca, Alejandra; Stefanini, Margarita Caruso (Saúde e Sociedade, 2022)
Biomedicine has built its object of study and intervention from a long and continuous process of desacralization, fragmentation, and progressive dissolution of the body as a monolithic entity in material and symbolic terms. Technological interventions provided possibilities for bodies, identities, and lives to be constructed, recombined, and designed by mobilizing molecular entities, which can be perceived as biofragments, with intervention practices. Consequently, in vitro fertilization technologies imply a tense and contradictory articulation of hegemonic meanings based on belief systems and norms about reproduction, genetic inheritance, kinship, identities, sexualities, nature, sanctity, bodies, and control and production of life. From ethnographic experiences in the area of assisted fertilization, this article analyzes the different dimensions and components that intervene in these procedures: when practices mobilize actors “allied” to the paternity and maternity project, the power and subalternity relations are made invisible in transactions. At the same time, these are essential for the material production of “hybrid parenthoods” in which particular contexts provide interpretations and sensibilities “situated” in the Argentine historical-political trajectory.